Writing ‘Anniversary’ in Historical Perspective: A Way to Find Identity - Sulistiyono, Singgih Tri; Amaruli, Rabith Jihan; Sarji, S. (Diponegoro University, 2023)
After the Reformation era, especially after implementing the Regional Autonomy Law, each regional government (city and province) in Indonesia has again conducted studies and re-established their ‘anniversary’. Besides focusing on legal and political aspects, historical perspectives in research and determining anniversaries can be used to find the regional identity. Based on it, regional governments can determine the direction of their development. Through the historical method and experience-based approach, this article focuses on the historical method in determining regional anniversaries.